Screening for Latent Tuberculosis in Children With Immune-mediated Inflammatory Diseases Treated With Anti-tumor Necrosis Factor Therapy: Comparison of Tuberculin Skin and T-SPOT Tuberculosis Tests - Saniye GİRİT,; Ayşe AYZIT ATABEK,; Ebru ŞENOL,; Tuba KOÇKAR KIZILIRMAK,; Sevgi PEKCAN,; Şafak GÖKTAŞ,; Sedat ÖKTEM,; Özgür KASAPÇOPUR,; Haluk ÇOKUĞRAŞ, (Archives of Rheumatology, 2020)
Objectives: This study aims to analyze the coherence between T-SPOT tuberculosis test (T-SPOT.TB) and tuberculin skin test (TST) with different cut-off values in screening latent tuberculosis infection (LTBI) both prior to and at the sixth month of anti-tumor necrosis factor (anti-TNF) treatment. Patients and methods: This prospective multicentric study included 57 children (34 girls, 23 boys, mean age 12.4±3.9 years; range, 6 to 18 years) diagnosed with immune-mediated inflammatory diseases (IMIDs) evaluated with TST and T-SPOT.TB for screening LTBI both prior to and at the sixth month of treatment with anti-TNF agents. Coherence between two tests was analyzed for TST cut-off values suggested by the local guidelines and also for different possible cut-off values of TST. Results: Tuberculin skin test was positive (≥5 mm) in 28.1% (n=16) of patients in the screening prior to treatment and in 33.3% (n=19) at the sixth month of treatment. T-SPOT.TB test was positive in 8.8% (n=5) of patients both prior to and at the sixth month of treatment. Coherence between two tests was poor or fair when compared with all possible TST cut-off values both prior to and at the sixth month of anti-TNF therapy. Conclusion: Our results show poor coherence between T-SPOT.TB and TST for all possible cut-off values of TST. Thus, using both tests would be beneficial in screening LTBI until further studies bring new evidence on the subject.